A comparative study of violence risk assessment tools: a systematic review and metaregression analysis of 68 studies involving 25,980 participants - Singh, J; Grann, M; Fazel, S (Elsevier, 2011)
There are a large number of structured instruments that assist in the assessment of antisocial, violent and sexual risk, and their use appears to be increasing in mental health and criminal justice settings. However, little is known about which commonly used instruments produce the highest rates of predictive validity, and whether overall rates of predictive validity differ by gender, ethnicity, outcome, and other study characteristics. We undertook a systematic review and meta-analysis of nine commonly used risk assessment instruments following PRISMA guidelines. We collected data from 68 studies based on 25,980 participants in 88 independent samples. For 54 of the samples, new tabular data was provided directly by authors. We used four outcome statistics to assess rates of predictive validity, and analyzed sources of heterogeneity using subgroup analysis and metaregression. A tool designed to detect violence risk in juveniles, the Structured Assessment of Violence Risk in Youth (SAVRY), produced the highest rates of predictive validity, while an instrument used to identify adults at risk for general offending, the Level of Service Inventory - Revised (LIS-R), and a personality scale commonly used for the purpose of risk assessment, the Psychopathy Checklist - Revised (PCL-R), produced the lowest. Instruments produced higher rates of predictive validity in older and in predominantly White samples. Risk assessment procedures and guidelines by mental health services and criminal justice systems may need review in light of these findings.